Túpac Amaru Cinema 2021: Emotions that survive architecture - Silva Tezén, Gianmarco André (2022)
In the context of the almost obsolescence of film buildings, with multiple old cinemas demolished, abandoned or serving as a refuge for criminality, it seeks to unearth the affections and emotions that such buildings were and still are capable of producing. This study focuses on the possible heritage value of the Túpac Amaru Cinema, a cinema located in the Comas district, a district born by the informal occupation of the territory, far from the center of the city of Lima. The hypothesis is that the affections and emotions that he aroused in his moment of glory persist despite his decline. Hence the title: “El Cine Túpac Amaru. Emotions that survive architecture”. On these motivations, a mainly qualitative research structure is proposed around the categories of context, object and subjects linked to heritage, thus favoring a phenomenological analysis. Finally, it is concluded that the Túpac Amaru Cinema contributed to consolidate the dynamics of the "neighborhood" in relation to its district (Comas), and much of the northern area of ​​Lima. However, if its symbolic and utilitarian dimensions are not reactivated, an important record of the history of Lima's people and of one of the most endearing episodes in the history of neighborhood / premiere cinemas in Peru may be lost.